Post-war reconstruction strategies of Ukraine: institutional and economic dimensions - Shpakova, Н.; Shpakov , A. (Ways to Improve Construction Efficiency, 2023)
The article examines a wide range of strategies and approaches to rebuilding Ukraine after the war. Historical examples of post-war recovery programs of countries in the 20th century are highlighted. Special attention is paid to the recovery of European countries in the context of using their experience, in particular the possibility of applying the "Marshall Plan" for modern Ukraine. The main advantages and disadvantages of recovery plans, conditions of their application, effectiveness in the economic and time dimension are considered. The article analyzes in detail the recovery plan of Ukraine, proposed by the Committee on Economic Development of the Verkhovna Rada. Taking into account the changes that took place at the front, in the structure of political elites and economic processes in the world and in Ukraine during the year after the publication of the plan, negative trends are singled out that distort the current and final results. The challenges facing Ukraine are examined in detail, including the extent of damage, geopolitical location, and the need for innovative technological development. The authors propose a comprehensive approach to recovery that includes reforming domestic policies, institutional structures, and attracting international support. Attention is also focused on Ukraine's integration into European economic structures, considering it as a key element for stable recovery. There are also warnings about the difficulties that Ukraine may face in the process of implementing the recovery plan, including economic and political obstacles. At the initial stage, the sequence and priority of the main measures should be established: demining huge areas of land, clearing debris, building shelters, dormitories and schools, medical facilities for providing basic medical care. These are the conditions for a quick start of reconstruction. The priority areas of development are singled out - "specialization of the country": the agricultural sector and the military-industrial complex. The article is a contribution to the discussion about the restoration of the country, because it focuses on modern challenges and potential ways of development, adaptability of the system to external and internal factors of influence, key moments of various cases of the plan for the revival of Ukraine in the post-war period.